2003
DOI: 10.1080/02697450310001632597
|View full text |Cite
|
Sign up to set email alerts
|

Studies of biological functions in blood cells from individuals with large platelets

Abstract: The present study was performed to explore differences in the expression of P-selectin and IL-8 production of blood cells in healthy individuals with large size platelets (MI-families) as compared to people having normal size platelets. A positive correlation between LPS-induced IL-8 production per platelet in whole blood and mean platelet volume (MPV) was found in the large platelet group (R=0.74, P<0.05). When the large and normal groups were combined the correlation was nearly, but not quite significant (R=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Our data are consistent with those of Villagra et al who found that the platelets of humans with SCD and pulmonary hypertension had increased sensitivity to activation with ADP and a PAR-1 thrombin receptor activating peptide (62). They did not report platelet size in their patients, but data from other studies in humans have demonstrated that large platelets are functionally more active (63).…”
Section: Discussionmentioning
confidence: 99%
“…Our data are consistent with those of Villagra et al who found that the platelets of humans with SCD and pulmonary hypertension had increased sensitivity to activation with ADP and a PAR-1 thrombin receptor activating peptide (62). They did not report platelet size in their patients, but data from other studies in humans have demonstrated that large platelets are functionally more active (63).…”
Section: Discussionmentioning
confidence: 99%
“…Antiplatelet agents have been shown to be effective for prevention of venous thromboembolic disorders, although to a smaller extent than anticoagulants [24,28]. Large platelets have a higher thrombotic potential than small platelets [11], and express higher levels of platelet activation markers, such as P-selectin [12]. Recently, increased levels of P-selectin have been shown in VTE patients [29], and a higher level of circulating P-selectin was associated with increased risk of recurrent VTE in patients with first unprovoked VTE [30].…”
Section: Discussionmentioning
confidence: 99%
“…Increased platelet volume is associated with increased platelet reactivity [9], shortened bleeding time [9], and increased platelet aggregation ex vivo [10]. Large platelets have higher thrombotic potential [11] and express higher levels of P-selectin [12] and glycoprotein IIbIIIa [13] than small platelets. Several studies have shown increased MPV in patients with coronary artery disease [14,15], and MPV has been identified as an independent risk factor for myocardial infarction and stroke [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, high mean platelet volume (MPV), which indicates platelet activation, has been shown to be an independent risk factor for cardiovascular events [12][13][14][15][16][17]. Plasma viscosity is another relatively easy index of rheology to measure and is also predictive of cardiovascular events [10,11].…”
Section: Introductionmentioning
confidence: 99%